Pemanfaatan Tanaman Obat Keluarga (TOGA): Pelatihan Pembuatan Teh Herbal Bagi Ibu-ibu PKK - Rahmawati, Nur; Fauziah, Fauziah; Kurniasih, Khamdiyah Indah; Kirana, Ade (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The term Family Medicinal Plants (TOGA) has become more popular in the last decade or so. Before this, family medicinal plants were better known as Living Pharmacy. Family medicinal plants have long been utilized in an effort to overcome health problems. Therefore, the utilization of TOGA needs to be developed and disseminated in the community, especially for housewives. Among the many family medicinal plants used by the community to maintain health is bay leaf. The utilization of bay leaves is processed as a healthy drink innovation, herbal tea in the form of tea bags because it is more practical and easy to make. Bay leaf herbal tea can be used to prevent cancer, lower cholesterol, increase the body's immune system, reduce the risk of kidney stones, maintain blood sugar levels and overcome stomach pain. The main target of this service is one of the PKK women's groups in Karangnanas Village, Banyumas Regency. who work as housewives. The purpose of this activity is to increase community understanding about traditional drinks from bay leaves that can reduce cholesterol. The results of this herbal tea making training activity increase good information to the community and can manage traditional beverage products made from bay leaves. With bay leaves being one of the alternative natural ingredients that can be utilized as traditional medicine to help treat diseases such as cholesterol, hypertension, gout, diabetes mellitus.